On geometric trilateral-free (n sub 3) configurations - Raney, Michael W. (Ars mathematica contemporanea, 2013)
This note presents the first known examples of a geometric trilateral-free ?$(23_3)$? configuration and a geometric trilateral-free ?$(27_3)$? configuration. The ?$(27_3)$? configuration is also pentalateral-free.
Keywords: configurations; trilaterals